Water Quality Monitoring and Wastewater Treatment Using the Constructed Wetland Concept at Bungva Lake, Kaysone Phomvihan City, Savannakhet Province, Lao PDR - Sacbouavong, Khoune; Norasane, Khonesavanh; Khoangvichit, Phoutthasone; Niravanh, Phukham; Phoutthavong, Thipsomphone; Lasachack, Khounphamy; Komthirath, Souphaphone (International Journal of Biosciences and Biotechnology; Vol 1 No 1 (2023): Special Issue February (Online First), 2023)
This study aimed to monitor physical, chemical, and biological water qualities to design a concept of a horizontal subsurface flow constructed wetland for wastewater treatment. The wetland is a small artificial wastewater treatment system consisting of one or more shallow treatment cells planted with wetland vegetation, which is usually suitable for warmer climates. The Standard Methods for the Examination of Water and Wastewater, 23rd Edition, published in 2017 by APHH, AWWA, and WEF, was used to analyze the ASPT index and water quality parameters. Temperature, pH, electrical conductivity, COD, BOD, and invertebrates were observed at three points at Bungva Lake Basin on March 16, 2021. Based on invertebrates (a water quality indicator), the three points had a water quality index value of 4.4, 3.8, and 3.6, respectively. It was also found that many human activities (agriculture, small industry, and settlement) and geological features control the lake’s water quality. Therefore, a horizontal subsurface flow constructed wetland is proposed as sufficient wastewater treatment for the lake